Azithromycin and Hydroxychloroquine combination: The future pharmacotherapy of COVID-19 - Shukla, Ananya; Mohabeer, Pornasha; Kashyap, Abhishek; Robinson, Jared; Banerjee, Indrajit (Journal of Biomedical Sciences, 2020)
Background: In response to the urgency of increasing death toll due to COVID-19, caused due to SARS CoV-2, various drugs are under clinical trial, as there is no specific drug for its treatment. In an international survey that was recently conducted in which about 7500 physicians participated from all over the world considered that Hydroxychloroquine and Azithromycin were among the most effective ones for the pharmacotherapy of COVID-19. Azithromycin is a macrolide antibiotic whose mechanism of action against COVID-19 is still unknown, but various theories have been postulated. In vitro and in vivo studies have been conducted; however, their results are quite contradictory. Azithromycin is said to increase the risk of QT prolongation in elderly patients and when given in combination with Hydroxychloroquine can increase the risk of Torsade’s de pointes. Therefore, caution has to be paid before prescribing Azithromycin. Conclusion: The mass loss of human lives is regrettable and needs to be stopped as soon as possible. Azithromycin could be the future drug for COVID-19, but such limited data is insufficient to support the drug's safety or efficacy and needs to be reconsidered.